Сутність та класифікація необоротних активів в контексті їх обліку - Ткаченко, Олександр Сергійович; Tkachenko, Oleksandr; Шатрава, Алла Володимирівна; Shatrava, Alla (Видавничий дім «Гельветика», 2024)
У статті розглянуто сутність і класифікацію необоротних активів підприємства в контексті їх обліку. Доведено, що класифікація необоротних активів є важливою для розуміння їхньої ролі у діяльності підприємства та забезпечення відповідного обліку. Запропоновано авторське визначення сутності необоротних активів, як ресурсів, які використовуються підприємством у довгостроковій перспективі і забезпечують стабільні економічні вигоди. В статті запропонована класифікація активів необоротних, котра дозволяє підприємству правильно вести облік, планувати амортизаційні витрати, оцінювати фінансовий стан та формувати стратегії розвитку. В статті згруповано фундаментальні етапи послідовності здійснення первинного обліку необоротних активів. Доведено, що первинний облік необоротних активів є ключовим елементом в управлінні майном підприємства, забезпечуючи його ефективне використання і збереження. The article considers the essence and classifcation of non-current assets of an enterprise in the context of their accounting. It is established that non-current assets are the foundation and basis for most types of business. It is proved that the classifcation of non-current assets is important for understanding their role in the activities of the enterprise and ensuring appropriate accounting and management. The author's defnition of the essence of non-current assets is proposed as resources that are used by the enterprise in the long term (more than one year) and provide stable economic benefts. The article proposes a classifcation of non-current assets, which allows the enterprise to correctly keep records, plan depreciation expenses, assess the fnancial condition and form development strategies. It is established that the primary accounting of non-current assets is the process of documenting, evaluating and registering assets when they are acquired or created. The article groups the fundamental stages of the sequence of primary accounting of non-current assets. It is proved that the primary accounting of non-current assets is a key element in managing the property of the enterprise, ensuring its effective use and preservation. Non-current assets of a business entity, on the one hand, are property that is separately owned by the enterprise, on the other hand, they are a resource that the enterprise controls and which allows it to receive economic benefts in the future. The most signifcant part of non-current assets is fxed assets and, we can say that they are what is used to produce a product. The state of non-current assets can be used to judge the property status of the enterprise and its equipment with means of production. Therefore, non-current assets are a key component of the activities of any enterprise, since they provide a material and intangible basis for long-term and stable work, they are strategically important for the enterprise, since they ensure its current activities and development. Their accounting and effective management contribute to the growth of proftability, competitiveness and fnancial stability of the organization.
The essence and features of the organization of the accounting of the fixed assets of the enterprise
Keywords: облік; accounting; активи; assets; необоротні активи; non-current assets; основні засоби; fxed assets; підприємство; enterprise; фінансова стійкість; fnancial stability; первинний облік; primary accountin